Determinants of going-concern audit opinions: Empirical evidence from listed mining firms in Indonesia - Hartanto, Maria Chruzita; Prajanto, Agung; Nurcahyono, Nurcahyono (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2023)
This study aims to ascertain how going concern audit opinions are affected by Profitability, liquidity, solvency, firm size, and audit quality. Profitability will be measured with Return on Asset, Liquidity with Current Ratio, Solvency with Debt to Asset Ratio, and Firm Size with Logaritma Natural of Total Assets. The data used in this study is secondary data. The mining businesses listed on the Indonesia Stock Exchange (IDX) in 2019–2021 comprise the study's population. Purposive sampling determines the sample, leaving 65 companies that satisfy the requirements. Logistic regression is the data analysis technique used in this study. In contrast, Audit Quality will be measured using the services of a public accounting firm hired by the company. The results indicate that while solvency had no impact on the going-concern opinion, variable Profitability, liquidity, firm size, and audit quality all significantly influenced going-concern opinion.